Peran Manusia dalam Dinamika Kehidupan: Perspektif Filosofis dan Sosiologis - Najma Hilyah Azla; Khansa Zahra Rukwida; Saskia Putri; Cintya Melati Putri; Wismanto Wismanto; Fitria Mayasari (Jurnal Kajian dan Penelitian Umum, 2024)
Humans play a crucial role in shaping the dynamics of life on Earth. From philosophical and sociological perspectives, humans are not only thinking entities but also members of society with social responsibilities. This research is driven by the desire to understand human contributions in addressing global challenges such as climate change, poverty, and rapid technological advancements. The main objective of this study is to analyze human existence within society from an interdisciplinary perspective to identify approaches that can enhance social harmony and global well-being. This study employs a qualitative method, conducting a literature analysis from various sources to explore existentialist ideas and the social responsibilities of humans. The analysis is performed in-depth to understand how individuals build social relationships and confront life’s challenges. The results indicate that humans, through their roles as agents of change, have substantial potential to foster societal welfare. This study concludes that a deeper understanding of human social roles can lay the foundation for a more harmonious and sustainable life.